The Mediating Role of Do-It-Yourself Behavior on the Effect of Perceived Economic Benefit, Lack of Quality, and Availability toward Customer Satisfaction in Medan Coffee Shops - Muhammad Fauzan Azhmy; Anggiat M. Situmeang; Ilham Mubaraq Ritonga (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the mediating role of Do-It-Yourself (DIY) Behavior in the relationship between Perceived Economic Benefit (PEB), Perceived Lack of Quality (PLQ), and Perceived Lack of Availability (PLA) on customer satisfaction in coffee shops in Medan City. The rapid growth of coffee shops has led to fierce competition and encouraged business owners to develop innovative marketing strategies. The research employed a quantitative associative approach with 100 respondents selected through probability sampling. Data were analyzed using Partial Least Square (PLS) with SmartPLS software. The results showed that PEB negatively affects DIY but positively affects satisfaction; PLQ and PLA positively affect DIY but negatively affect satisfaction. DIY behavior negatively influences satisfaction and mediates the relationship between the independent and dependent variables. The findings emphasize that DIY strategies do not always increase satisfaction, suggesting that professional promotion and consistent quality should still be prioritized.